Android-Based Media Development For Memorizing Arabic Verbal Conjugation and Its Functional Meaning - Romadhon, Muh. Syahri; Khasairi, Moh; Tohe, Achmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Changes in the morphological construction of Arabic words (wazn al-ṣarf) produce new meanings, often making Arabic learners fall into translation errors. While the existing books on ṣarf (Arabic morphology) have explained these meanings narratively, the learners have yet to face a massive problem in tracking these morphological construction-based meaning changes. Therefore, as a novelty offered, this research aims to identify the changing meanings based on the varied morphological constructions and represent them in a didactic poetic arrangement to ease learning and memorization. The development design is organized based on 4D procedures (Define, Design, Develop, and Disseminate). The method used in this research is descriptive qualitative. Several morphological constructions of Arabic words and their resulting meaning changes were identified in the defining stage. The design stage was concerned with determining the prosodic form of naẓm (didactic poetic versification, ʽarȗḍ) with which the identified meaning changes of the varied morphological constructions of words were composed and devising the procedures by which this composed naẓm was tested to validate its utility in helping learning and memorization processes, in terms of its feasibility, media appearance, and teaching steps. In the developing stage, the prosodic form of Rajz was chosen to compose the naẓm, and an Android-based application was selected as the learning medium. Finally, in the disseminating stage, the produced application was uploaded to the Google Play Store, which learners, teachers, and validators can download for testing and use. The research produced a naẓm consisting of 9 chapters of morphological word constructions and 32 verses. The validation test suggested a very good qualification (87,61%), with some revisions in certain parts. As such, the product of this research is recommended to be used by both teachers and learners of Arabic to comprehend and memorize more effectively the different meanings of various morphological constructions of Arabic words using a naẓm.